Admission Test as Predictor of Performance of Students in the English Subject - Ocbian, Magdalena M.; Gamba, Michael P.; Ricafort, Jhonner D. (JPAIR Institutional Research, 2015)
Admission testing is an integral part of higher education institutions (HEIs) in maintaining the quality educational standards. Through testing, the HEI’s can objectively select applicants that are likely to succeed in their intended course. The study was conducted to determine the predictive validity of the admission Tests of the secondary and college levels to their performance in English subjects using the descriptive-correlational designs. The respondents were the secondary students of the SSC Laboratory High School and First-Year college students from school years 2009-2012. The Pearson Correlation was used to determine the relationship of the admission test results and the performance of the identified respondents on the English subject. The GPA on English and SSC Admission test results on college level shows a moderate positive relationship. Also, high school level denotes a strong positive relationship. This relationship had been manifested in 40% of the respondents in secondary level, and 13% of the respondents in college level. This significant relationship suggests that admission test determines the potential performance of the students in their English subject in both secondary and tertiary level. Thus, it was concluded that SSC Admission Test is a valid predictor of the students’ performance in English subject.